Challenges of Government Ethics in Human Resource Governance in Village Government in the Digital Era - Hikmah Muhaimin; Azzara Rum Mawangi; Desi Nur Vitasari; Nasihul Amin (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
Government ethics is a set of standards that regulate the behavior of officials in carrying out their responsibilities. These standards are based on important values, including accountability, integrity, and morality. Implementing this code of ethics is important to improve the performance of government organizations, especially in the context of Industry 5.0 and the digital era. Qualitative methodology and case study design were used to conduct research in Village Government. The results show that digitalization has an impact on human resource governance in villages which in turn has an impact on changes in data administration, work methodology and competencies. To achieve success in the context of digital transformation, it is necessary to increase digital literacy and apply information and communication technology in rural areas. The aim of this research is to increase the competitiveness and welfare of villages, as well as increase the effectiveness of human resource management in village government, encouraging the progress of sustainable and efficient government ethics in the digital era and Industry 5.0.